Analisis Fenomena Childfree di Era Gen Z terhadap Syariat dan Realitas Modern - Salsabilla Yessino; Diva Mutiara Sulaiman; Abdul Fadhil (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The phenomenon of childfree has become an increasingly discussed topic in Indonesian society, especially after public figures like Gita Savitri openly expressed their decision not to have children. This phenomenon is related to various factors, including past trauma, concerns over overpopulation, economic instability, and the evolving mindset of Generation Z, which is more realistic and focused on personal freedom. However, the decision not to have children also presents challenges, especially from a religious perspective, particularly Islam, which teaches that having offspring is both a blessing and an obligation. This research aims to analyze the childfree phenomenon from an Islamic perspective by examining the principles of Sharia and the relevance of childfree to fiqh rulings such as ‘azl. The research findings indicate that while childfree contradicts religious views on the obligation to have children, the phenomenon can still be understood within the framework of reproductive rights granted to married couples in Islam. This study is expected to provide a deeper understanding of the childfree phenomenon and its relationship with Islamic principles.